Four-Year and Five-Developing-Stage Dynamic QTL Mapping for Tiller Number in the Hybrid Population of Agropyron Gaertn. - Che, Yonghe; He, Yutong; Song, Nan; Yang, Yanping; Wei, Lai; Yang, Xinming; Zhang, Yan; Zhang, Jinpeng; Han, Haiming; Li, Xiuquan; Zhou, Shenghui; Liu, Weihua; et al. (Frontiers in Plant Science, 2022)
Tiller number (TN) is an important agronomic trait affecting gramineous crop yield. To understand the static and dynamic information of quantitative trait loci (QTL) controlling TN of Agropyron Gaertn., unconditional and conditional QTL mapping of TN were conducted using a cross-pollinated (CP) hybrid population with a total of 113 plant lines from the cross between A. cristatum (L.) Gaertn. Z1842 and A. mongolicum Keng Z2098, based on the phenotypic data of TN at five developmental stages [recovering stage (RS), jointing stage (JS), heading stage (HS), flowering stage (FS), and maturity stage (MS)] in four years (2017, 2018, 2020, and 2021) and the genetic map constructed of 1023 single-nucleotide polymorphism (SNP) markers. Thirty-seven QTL controlling TN were detected using two analysis methods in four years, distributed in six linkage groups. Each QTL explained 2.96%–31.11% of the phenotypic variation, with a LOD value of 2.51–13.95. Nine of these loci detected both unconditional and conditional QTL. Twelve unconditional major QTL and sixteen conditional major QTL were detected. Three relatively major stable conditional QTL cQTN1-3, cQTN1-5, and cQTN4-1 expressed in 2020 and 2021. Meantime, two pair major QTL cQTN1-5 and qTN1-4, cQTN2-4, and qTN2-3 were located at the same interval but in different years. Except for qTN2-2 and qTN3-5/cQTN3-5, other thirty-four QTL were first detected in this study. The study would provide a better interpretation of genetic factors that selectively control tiller at different development stages, and provide a reference for molecular marker-assisted selection in the related plant improvement.